LIST OF SITUATIONS-PROBLEM OF FUTSAL (LSPF) AND THEIR SOLUTIONS: DEVELOPMENT OF VISION IN REASONING TACTICAL TRAINERS TEAM OF ADULT (Fiep Bulletin - online, 2013)
This study was axis guiding with the task of cast, under the indoor soccer, the most common situations tactics, which cause problems to those running the game on the outside (coaches) and those who execute the decisions of these (athletes). We collected data from each coach (n = 12), and then examined the responses most cited throughout scanning. The results showed a latent concern with regard to the question-line and goalkeeper were discussed as providing important knowledge for the formation of methodologies for the teaching of the tactics of play.